BENEFITS AND RISKS OF ULIPRISTAL ACETATE FOR UTERINE FIBROIDS - Triasti Khusfiani; Yudhisman Imran; Irmiya Rachmiyani; Donna Adriani (Jurnal Akta Trimedika, 2025)
Uterine fibroids (FU) are often experienced by women of reproductive age or in their early menopause with therapy options involving surgical intervention such as hysterectomy. Ulipristal Acetate (UPA) is an oral drug from the selective progesterone receptor modulator (SPRM) class which has been proven to be effective in treating FU symptoms so that patients can maintain their fertility and their uterus. The PEARL I-IV clinical trials (PGL4001/UPA Efficacy Assessment in Reduction of Symptoms Due to Uterine Leiomyomata) has proven the effectiveness of this drug in terms of reducing symptoms such as bleeding and pain, reducing fibroid volume, as well as its impact on the patient's quality of life. During ongoing clinical trials, the majority of side effects found were mild-moderate and reversible. In 2020, UPA was discontinued due to reports of the risk of DILI (drug induced liver injury), but after thorough investigation and considering its benefit and risk ratio for patients, UPA can be given again but its indication is limited to intermittent FU therapy with moderate to severe symptoms in women who has not reach menopause or when surgical procedures cannot be performed/have failed. Close monitoring of liver function is of course necessary.